2021
DOI: 10.14309/ajg.0000000000001343
|View full text |Cite
|
Sign up to set email alerts
|

Obeticholic Acid and Fibrates in Primary Biliary Cholangitis: Comparative Effects in a Multicentric Observational Study

Abstract: INTRODUCTION: Obeticholic acid (OCA) and fibrates therapy results in biochemical improvement in placebo-controlled trials in patients with primary biliary cholangitis and insufficient response to ursodeoxycholic acid. There is scarce information outside of clinical trials. Therefore, we have assessed the effectiveness and adverse events of these treatments. METHODS: Data from patients included in the ColHai registry treated with OCA, fibrates, or both w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…In 2017, the EASL Clinical Practice Guidelines proposed various criteria as tools to select patients for second-line therapies and for a better design of clinical trials in PBC [6]. Multiple clinical trials were conducted to determine the safety and efficacy of other drugs such as OCA, bezafibrate, and elafibranor, in patients with incomplete response to UDCA [22][23][24]. Most clinical trials defined incomplete response in patients who were treated with UDCA at least for 12 months [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the EASL Clinical Practice Guidelines proposed various criteria as tools to select patients for second-line therapies and for a better design of clinical trials in PBC [6]. Multiple clinical trials were conducted to determine the safety and efficacy of other drugs such as OCA, bezafibrate, and elafibranor, in patients with incomplete response to UDCA [22][23][24]. Most clinical trials defined incomplete response in patients who were treated with UDCA at least for 12 months [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Reig et al . [96] reported that pruritus was the most common side effect of obeticholic acid in PBC patients. This is similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the EASL Clinical Practice Guidelines proposed various criteria as tools to select patients for second-line therapies and for a better design of clinical trials in PBC (6). Multiple clinical trials were conducted to determine the safety and e cacy of other drugs such as OCA, beza brate, and ela branor, in patients with incomplete response to UDCA (22)(23)(24). Most clinical trials de ned incomplete response in patients who were treated with UDCA at least for 12 months (25, 26).…”
Section: Discussionmentioning
confidence: 99%